Rainout shelters on SGS - Sprague, Sallie, photographer (Colorado State University. Libraries, 2008)
Rainout shelters constructed and used by Knapp grad student Cherwin on the SGS, wide angle view.
Keywords: equipment; SGS; experiments; landscapes